Herbal Extracts as Neuroprotective Agents in an In-vitro Model of Aluminum Neurotoxicity - Ezzelarab, Nada (AUC Knowledge Fountain, 2021)
Background: Aluminum toxicity due to environmental or industrial exposure, medical applications, or from cooking utensils is a serious medical problem. The current study aims to investigate three herbal extracts: pomegranate peel extract, Achillea fragrantissima extract, and papaya fruit extract to combat this neurotoxicity. Methods: Chemical characterization of the three extracts were evaluated using HPLC MS while their neuroprotective activity was assayed using MTT assay on SHSY5Y cells and nitric oxide levels. Results: Using HPLC-MS chromatography, we have identified twenty-one compounds in the hydro-alcoholic Achillea fragrantissima, seventeen were determined in the pomegranate peel, eleven were assessed in the Carica papaya ethanolic extract, and eight in the aqueous extract. Pomegranate peel extract was safe on neuroblastoma cells at doses 10, 50 µg/ml, Achillea fragrantissima aerial parts were safe up to 100 µg/ml, and Carica papaya fruit extract was safe up to 1000 µg/ml. Our investigation proved that the IC50 of AlCl3 is 1 mM AlCl3 (p-value < 0.0001). Pomegranate 50 µg/ml increased cell viability from around 50% to 92% (p-value < 0.0001), 50 µg/ml of Papaya improved the cell viability to above 100% (p-value < 0.0001) and 50 µg/ml Achillea fragrantissima boosted the cell viability from 50% to around 100% (p-value < 0.0001). While Aluminum chloride at dose 1000 µM (240ug/ml) has increased the nitrite levels to around 11.4 µM (0.52 ug/ml), which is 8 folds in comparison to the negative control (p-value < 0.001), pretreatment of cells with Achillea fragrantissima, Pomegranate, and Papaya at doses 50 µg/ml has decreased the nitrite levels to 8.1 (p-value < 0.05), 5.7 (p-value < 0.01) and 2.5 µM (p-value < 0.001), (0.37, 0.26 and 0.11 µg/ml), respectively Conclusion: Our in vitro investigation showed that the tested extracts have potential neuroprotective activity against Al-induced neurotoxicity. Public awareness should be raised about the negative impact of Aluminum use, especially as cooking utensils.